2012
DOI: 10.1177/0267658312452066
|View full text |Cite
|
Sign up to set email alerts
|

L2 acquisition of Bulgarian clitic doubling: A test case for the Interface Hypothesis

Abstract: The purpose of this study is to expand the testing ground of the Interface Hypothesis (Sorace, 2006) by investigating the degree to which second language (L2) learners of Bulgarian with English as their first language (L1) had acquired the pragmatic function of clitic doubling as a topicality marker. Advanced and intermediate L2 speakers of Bulgarian, as well as a control group of Bulgarian native speakers, participated in the experiment. The experimental materials included a proficiency test and a pragmatic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 28 publications
4
51
0
2
Order By: Relevance
“…The acquisition of Ø topic provides further evidence to the claim that some aspects at the syntax-discourse external interface are acquirable (Ivanov 2012;Iverson et al 2008;Kraš 2008;Rothman 2007Rothman , 2009Slabakova et al 2012;Slabakova and Ivanov 2011;Zhao 2008Zhao , 2012a. The current study supports the proposals of White (2011) andYuan (2010) that interface vulnerability may not be domain-wide in that Ø topic at the syntax-discourse interface is acquired in comparison with some syntax-discourse properties that have proved to be vulnerable to ultimate fossilisation as discussed in Sorace and Filiaci (2006), among others.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The acquisition of Ø topic provides further evidence to the claim that some aspects at the syntax-discourse external interface are acquirable (Ivanov 2012;Iverson et al 2008;Kraš 2008;Rothman 2007Rothman , 2009Slabakova et al 2012;Slabakova and Ivanov 2011;Zhao 2008Zhao , 2012a. The current study supports the proposals of White (2011) andYuan (2010) that interface vulnerability may not be domain-wide in that Ø topic at the syntax-discourse interface is acquired in comparison with some syntax-discourse properties that have proved to be vulnerable to ultimate fossilisation as discussed in Sorace and Filiaci (2006), among others.…”
Section: Discussionsupporting
confidence: 82%
“…Ivanov (2012) shows that advanced English-speaking learners have acquired the pragmatic meaning of clitic doubling in Bulgarian. Iverson et al (2008) report that advanced L2 learners of Spanish have acquired the discourse-dependent distinction between the indicative and subjunctive complements with epistemic predicates.…”
Section: Introductionmentioning
confidence: 95%
“…Subsequent research has documented similar asymmetries with respect to other linguistic phenomena (Belletti & Leonini, 2004;Lozano, 2006;Valenzuela, 2006). However, other empirical studies have either failed to detect any apparent signs of instability in domains predicted by the Interface Hypothesis to be vulnerable or suggested that such interface-related difficulties are not pervasive (Donaldson, 2011(Donaldson, , 2012Ivanov, 2012;Iverson, Kempchinsky, & Rothman, 2008;Leal Méndez, Rothman, & Slabakova, in press;Slabakova & Ivanov, 2011;Slabakova, Kempchinsky, & Rothman, 2012). Researchers have also challenged some aspects of the hypothesis on theoretical grounds, including the imprecise formulation of the proposal, difficulty of distinguishing interface-related phenomena from noninterface-related phenomena (and, by the same token, external interfaces from internal interfaces), difficulty of positioning the hypothesis within specific theoretical models of language architecture, and potentially an overly "restrictive" focus of the proposal, originally formulated only for some bilingual populations and not others (Domínguez, 2013;Montrul, 2011;Rothman, 2009;Rothman & Slabakova, 2011;White, 2011).…”
Section: Interfaces: the Integration Problemmentioning
confidence: 95%
“…Arregui 2003, Contreras 1976, Casiellez-Suárez 2004, Suñer 2006, Zubizarreta, 1998 and tested in empirical studies using native and non-native populations in multiple languages (e.g. Donaldson 2011, Ivanov 2012, Valenzuela 2006, CLRD has been only occasionally discussed in the formal literature (Cecchetto 1999, López, 2009, Villalba 2011). In addition, there has been a scarcity of empirical studies involving this structure (but see Slabakova et al 2011, for L2 acquisition).…”
Section: Spanishmentioning
confidence: 99%